EFFECTIVE MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS IN IMPROVING THE ORGANIZATION OF INDEPENDENT WORK OF LEARNERS - Baldzhy , M. D. (The actual problems of regional economy development, 2024)
The article discusses the benefits of improving the independent work of students in higher education institutions to achieve quality results in the educational process, which defines the research topic. It is argued that improving the organization of independent work of learners will positively influence the effective management of higher education institutions. The theoretical basis of students' independent work as a form of organizing the educational process is systematized, the advantages of implementing didactic conditions for effective independent work of students are outlined, and levels of student independent activity are determined. The components characteristic of independent work, including motivational links, setting specific tasks, choosing methods of execution, execution, and control, are identified. The experience of European countries in organizing the independent work of learners is examined, which indicates a close connection between the educational process and the market, production, and possible areas of future student activity. The application of various forms of organizing students' independent work, depending on the specialty and educational programs offered by departments when developing discipline work programs, taking into account the needs of stakeholders and the labor market, is justified. The aim of the article is to analyze existing approaches to students' independent work and improve its organization for effective management of higher education institutions. Various scientific methods were used in the research and solution of the tasks, the main ones being systematization, comparison, analysis, questionnaires, and graphical analysis. As a result of the conducted study of the organization of independent work in higher education institutions, the positions of learners and teachers were determined, which generally have common views on the need to improve the identified problem. Specific steps to improve this form of the educational process were identified through the analysis of anonymous questionnaires of students and teachers. The scientific novelty lies in the connection between improving the organization of independent work of learners and effective management of higher education institutions, which allows asserting the improvement of the quality of educational services and the improvement of the educational process through the improvement of the independent work system. The practical significance of the study lies in the application of existing developments to improve the existing system of organizing students' independent work, aimed at training highly qualified specialists in various fields for the further development of society and the country.